2006
DOI: 10.1214/lnms/1196285827
|View full text |Cite
|
Sign up to set email alerts
|

Finitary Codes, a short survey

Abstract: In this note we recall the importance of the notion of a finitary isomorphism in the classification problem of dynamical systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Being finitary is a locality condition, and for other natural notions of locality, we refer the reader to [MS22] (in their more refined framework, what we called finitary above is called stop-finitary ). Note also that the classic example of isomporhism between Bernoulli shifts by Meshalkin ([M59]) is also a finitary one and that in [KS79], Keane and Smorodinsky proved the existence of finitary isomorphisms between Bernoulli shifts of the same entropy over , and thus strengthening Ornstein’s landmark theorem (for a survey of finitary codings in this direction, see [S06]).…”
Section: The Case Of Finitary Smentioning
confidence: 99%
“…Being finitary is a locality condition, and for other natural notions of locality, we refer the reader to [MS22] (in their more refined framework, what we called finitary above is called stop-finitary ). Note also that the classic example of isomporhism between Bernoulli shifts by Meshalkin ([M59]) is also a finitary one and that in [KS79], Keane and Smorodinsky proved the existence of finitary isomorphisms between Bernoulli shifts of the same entropy over , and thus strengthening Ornstein’s landmark theorem (for a survey of finitary codings in this direction, see [S06]).…”
Section: The Case Of Finitary Smentioning
confidence: 99%
“…Mappings satisfying the property in the question are said to be finitary (see [32] and [15] for more information).…”
Section: Theorem 2 the Time-one Map Of A Topologically Weak Mixing Su...mentioning
confidence: 99%
“…Aperiodic finite-state Markov processes are finitarily isomorphic to BSs (are fB ) (see [3]). In unpublished work, Smorodinsky showed that every finitary factor of a BS has exponentially decaying return times (see [9] for more details). Countable state mixing Markov processes with exponentially decaying return times are fB (see [7]).…”
mentioning
confidence: 99%
“…Countable state mixing Markov processes with exponentially decaying return times are fB (see [7]). For an up-to-date survey of the literature on finitary maps, see [9].…”
mentioning
confidence: 99%